Pengaruh Teknik Pijat Oketani Terhadap Produksi Air Susu Ibu (ASI) Pada Ibu Post Partum Di Ruang Edelweis Rumah Sakit Umum Daerah (RSUD) Kota Cilegon Tahun 2023 - Indah Nurfazriah (Lembaga Pengembangan Kinerja Dosen, 2022)
Based on preliminary study of 5 post partum mothers who had breastfed their babies 1x24 hours found 4 (80%) mothers with insufficient milk production marked by tense, hard mother's breasts with a volume of milk production <5ml. The inability to produce sufficient breast milk can be prevented in many ways, one of them by using massage techniques at certain points. This study aims to analyze the effect of oketani massage techniques on breast milk production in post partum mothers in the Edelweis Room of the Cilegon Hospital. The research design uses the method pre-experimental the one group pre-test and post-test design. The sample uses primary data, namely post partum mothers according to the inclusion and exclusion criteria as many as 28. The analysis used a non-parametric statistical test, namely Wilcoxon Test. The independent variable in this study was oketani massage, meanwhile the dependent variable was the milk production postpartum mothers. The results of the univariate study showed that the average milk production before the oketani massage was 1.5 ml (95% CI: 1.2-1.7) meanwhile the average milk production after the oketani massage was 6.1 ml (95% CI: 5) ,6-6,5), Results analysis wilcoxon with a sig value of 0.000<α (0.05) which means that there is a significant effect between the oketani massage before and after on milk production in post partum mothers. These results indicate that it is necessary to introduce the oketani method, either through training or workshops as an effort to increase milk production in post partum mothers.